PENGARUH PARIWISATA TERHADAP KEHIDUPAN SOSIAL BUDAYA PESISIR di Kawasan Taman Nasional Bali Barat dan Taman Wisata Pulau Menjangan - Ernawati, Ni Made (Fakultas Ilmu Budaya Universitas Diponegoro, 2011)
Province of Bali is the main destination for foreign tourists to Indonesia. Bali's tourism sector is most developed with diverse attractions such as the natural attractions of West Bali National Park and Menjangan Island Marine Park. Development of Tourism in West Bali National Park and Menjangan Island Marine Park has positive and negative impacts which are not significant to the economy and socio-cultural life of the local community because most people are not dependent on the tourism sector.